INTERAKSI JENIS PENUTUP DENGAN LAMA PAPARAN SINAR MATAHARI TERHADAP SUSUT BOBOT, KANDUNGAN KAROTENOID DAN VITAMIN A WORTEL (Daucus carota L.) - Triningsih, Desy Wulan; Prihastanti, Erma; Haryanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
Carrots (D. carota L.) are root vegetable and the source of carotenoids. Careless handling during post-harvest such letting carrots exposed to sunlight leads to damage in carrots. Those effects can be reduced by covering treatment. This study aimed to determine the interaction between cover type and duration of sun exposure on the wet weight, carotenoids and vitamin A content of carrots. Local carrot cultivar in Sidomukti Village, Bandungan, Semarang were studied. The study conducted at the Laboratory of Plant Physiology, FSM, Diponegoro University. The experiment was laid out in Complete Randomized Design (factorial) with two factors: cover type (P) and duration of sun exposure (T). Data were analyzed for ANOVA, followed by Duncan's test (95% confidence level). Wet weight, carotenoids and vitamin A content were recorded. The results showed the cover type and duration of sun exposure influence the wet weight, carotenoids and vitamin A content of carrots. Duncan test results showed significant differences. Losses can be reduced by aluminum foil cover and not exposed carrots to sunlight. Impenetrable cover should be used and exposure to the sun should be avoided for more than 6 hours after harvest to enhance carrot qualities retention